THE FUTURE OF AI-INTEGRATED ART EDUCATION - Kaur, Gurpreet; Das, Satya Ranjan; Kapoor, Tarun; Upadhyay, Satish; Divakaran, Prakash; Aggarwal, Prateek (ShodhKosh: Journal of Visual and Performing Arts, 2025)
With artificial intelligence (AI) and the art education together alters how individuals are taught to be creative and express themselves using art. The application of AI technologies in art classes changes how students create, interpret, and discuss art due to the development of smarter technologies. The history of AI-integrated art education is considered in this paper, starting with the introduction of the first digital tools and ending with the development of intelligent creative systems. This is demonstrating that AI is emerging as a more of a creative partner and it is assisting students and artists to experiment with new styles, methods and approaches across other areas. The paper examines the ways machine learning algorithms can support the appearance of new ideas and push the boundaries of the artistic practice based on examples of artworks supported by AI. In the classes where AI is introduced into the classroom, training techniques should be reconsidered during art classes. Teachers are replacing the traditional skills based lessons with concept based lessons that are more centered on interpretation, imagination, and social responsibility. Elements like generative design, adaptable learning environments and creative coding software are reimagining the way AI-founded platforms work to enable learning through giving a student-optimized, data-driven input. Nevertheless, AI usage is not without its issues, including accessibility issues, digital equality, writing ethics and freedom of art. The future of art education will be AI, whereby the systems will be adaptable to all people and at the same time balanced with human senses and computer intelligence. The paper projects a vision of AI-powered learning environments in which AI is perceived as a tutor to students and a colleague, which addresses the necessity of students to understand the interrelatedness of art, technology, and society.